1978
DOI: 10.1111/j.1748-1716.1978.tb06049.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue osmolality in intestinal villi during luminal perfusion with isotonic electrolyte solutions

Abstract: A cryoscoptic technique has been developed that makes it possible to determine tissue osmolality in the core of the intestinal villi. During absorption from an isotonic electrolyte solution containing glucose an osmolality gradient was demonstrated from tip to base of the villi in both the jejunum and the ileum. The tissue osmolality at the villous tips was measured to 1 000-1 200 mOsm/kg H2O while the osmolality at the villous base was approximately isotonic with plasma. Increasing intestinal blood flow by i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…Interestingly, while potassium is reduced in the HSD feces, the magnitude was not equivalent to the sodium elevation. However, since the normal osmolar gradient that exists from the villus tip to the villus base exceeds the osmoles of both sodium and potassium in the content, it is likely other osmolytes contribute to water absorption (32). …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, while potassium is reduced in the HSD feces, the magnitude was not equivalent to the sodium elevation. However, since the normal osmolar gradient that exists from the villus tip to the villus base exceeds the osmoles of both sodium and potassium in the content, it is likely other osmolytes contribute to water absorption (32). …”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the villous tip contained 3-4 times as much sodium per unit weight protein as the villous base, implying that a considerable hyperosmolarity may exist at the tip portion of the villus (Jodal et al 1978). The renal medulla is routinely exposed to a greatly hyperosmotic extracellular fluid (Isabelle et al 1994), and hyperosmotic plasma is observed in chronic hypernatremia (Papadimitriou et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Cryoscopic techniques used in determining tissue osmolality indicate that during active absorption the lamina propria underlying the villus tips obtains a tissue osmolality of 1,000 to 2,000 mOsm [14]. Moreover, as one approaches the pericrypt lamina propria, this hyperosmolal gradient progressively diminishes [14].…”
Section: Significance Of Asymmetric Partitioning Of Paracellular Condmentioning
confidence: 98%